WEB DEVELOPMENT AS A DRIVER OF REAL ESTATE PROJECT PROMOTION AND CUSTOMER ENGAGEMENT - Aram Andreasyan (Modern American Journals, 2025)
The modern real estate market is experiencing rapid Digitalization. In this process, web development serves as a key tool for promoting projects, attracting target audiences, and improving the effectiveness of communications between developers and potential buyers. This article analyzes the main approaches to using web technologies in real estate, examining their advantages and current industry trends.
Keywords: Central Asia, socio-political values, political integration, soft power, historical unity, intercultural dialogue, youth policy, historical heritage, cooperation, diplomacy, public diplomacy, social stability.